Centering and uplifting youth voice in planning for a more resilient climate future in rural Colorado: a case study of a student resilience team asking for change - Schloesser, Katya; Davis, Ravi; Ruffin, Taylor; Gold, Anne U.; Christensen, Alicia; Littrell, Megan K.; Boyd, Kathryn J. (Frontiers in Climate, 2024)
Rural communities are increasingly facing challenges from climate-related natural hazards such as drought, wildfire, and flood. These cascading hazards threaten social, emotional, physical, and economic well-being, and pose unique challenges to rural areas which may already struggle to find enough resources. Yet, rural areas are rich in social capital, creativity, and resilience, and future leaders are learning how to build agency and increase their community’s resilience in school settings. Students in Estes Park, Colorado, have experienced major climate-fueled hazards in their lifetimes, surviving the floods in 2013 and the East Troublesome and Cameron Peak wildfires in 2020. At Estes Park Middle School, the Environmental Resilience Team (ERT) is an afterschool group of students who are actively participating in promoting public awareness, mitigation, and policy-making to increase resilience to natural hazards. Supported by the Hazard, Education, Awareness, and Resilience Task Force (HEART Force) Program, a comprehensive curriculum that immerses students in the study of their community’s resilience to floods and fires, in conjunction with the Earth Force Environmental Civic Action resources, students and educators gained the tools needed to spearhead community discussions on resilience, all while striving to mitigate and minimize future risks. In this paper, we tell the story of the Environmental Resilience Team’s campaign to pass statewide legislation to implement Wildland Urban Interface (WUI) Building Codes in high-risk areas. Students visited the Colorado State Capitol, met with their State Senator and Governor to lobby for the passage of the bill. This initiative builds upon years of action projects, including service projects to mitigate fire risk in vulnerable populations within the mountain town of Estes Park and build community education and awareness through the distribution of “go-bags” to community members. By including youth voice in public decision-making and planning for climate resilience, community leaders and policymakers can develop more holistic plans that include multigenerational input. This research is part of a broader study across implementations of HEART Force in several classrooms that showed that the HEART Force program helped students develop a sense of agency and grow in their understanding of community resilience.